Kewenangan Badan Perencanaan Pembangunan Daerah (BAPPEDA) Dalam Mewujudkan Penataan Ruang Yang Baik Di Kota Pekanbaru - M Syarif Hidayatullah; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Spatial structures and patterns that are not well implemented in Pekanbaru City in accordance withLaw No. 26 of 2007 concerning Spatial Planning, of course will lead to many problems in spatial planningthat occur in Pekanbaru City. Problems caused by the lack of spatial planning in Pekanbaru City such as;floods, traffic jams, air pollution, land use that is not in accordance with its designation and many otherproblems related to spatial planning that have an impact on the level of welfare of the people of PekanbaruCity. In order to realize good autonomy and spatial planning, the need for the Regional DevelopmentPlanning Agency (BAPPEDA) in carrying out its authority from the formulation of regional planningpolicies, preparation of plans that contain the vision, mission, goals, strategies, policies, programs andcoordinate the development activities of each Regional Work Unit (SKPD).The type of research that the author uses is juridical sociological research approach that emphasizesthe legal aspects related to the subject matter to be discussed, related to the reality that occurs in the field.In this case the authors conducted research on the Pekanbaru City Regional Development Planning Agencyand the Pekanbaru City Public Works and Spatial Planning Office regarding the problems of spatialplanning in Pekanbaru City.From the results of this study it can be concluded that there are three main problems. First, theauthority of BAPPEDA Pekanbaru City in realizing good spatial planning is regulated in PERMENDAGRINo. 86 of 2017 concerning Procedures for Planning, Controlling and Evaluating Regional Development,Procedures for Evaluating Long-Term Regional Development and RPMJD, and Procedures for ChangingRPJPD, RPJMD and RKPD, and PERWAKO Pekanbaru City No. 116 of 2016 concerning the Position,Organizational Structure, Duties and Functions and Work Procedures of BAPPEDA Pekanbaru City,BAPPEDA Authority After the issuance of PP No. 18 in 2016. The two factors that hamper BAPPEDAPekanbaru City are the Pekanbaru City Spatial Plan that does not yet exist, the inconsistency between theprogram and the implementation of the Pekanbaru City administration in the RPJDD, RPJMD and RKPDdocuments, the political interests of several parties, the rationalization of the budget and the building Thereare already three attempts that can be done by BAPPEDA in realizing good spatial planning in the city ofPekanbaru, which are spatial planning, spatial use, spatial use control, PERMENDAGRI No. 116 of 2017concerning the Regional Spatial Planning Coordinating Team, approaching regional development planningwell, following the rules of the formulation of regional development planning policies and regional policiesto issue regulations on Pekanbaru City's spatial planning.Keywords: Authority, BAPPEDA, Spatial Planning.